Total Physical Response And Paraphrasing Method In The Development Of Teaching Material For The Maritime English Subject At Shipping Vocational School - Listriyawati, Nyoman Ardiana; Kuncowati, Kuncowati; Perwira, Hammam Satya (Politeknik Bumi Akpelni, 2024)
For some marine cadets in vocational high school, one of the difficulties in learning English is listening, whereas the students lack concentration, understanding, and vocabulary. Employing suitable learning methods that will help the students improve their skills in listening is expected to overcome the student’s lack of concentration, understanding and vocabulary. In this research, the researchers will find out whether total physical response and paraphrasing as learning methods can improve cadets’ listening skills. A qualitative method was used in this research, involving sixty marine cadets as the respondents. The finding revealed that both methods Total Physical Response and Paraphrasing have a significant impact on the development of Maritime English teaching materials for shipping cadets, with some improvement on indicators that should be added to enhance The Maritime English teaching materials.